Rational Design of a Biomimetic Cell Penetrating Peptide Library - Karagiannis, Emmanouil D. (2013)
Cell penetrating peptides have demonstrated potential to facilitate the cellular delivery of therapeutic molecules. Here we develop a set of 50 cell penetrating peptide based formulations with potential to deliver small interfering RNAs intracellularly. The transfection efficacy of siRNA containing lipid-like nanoparticles decorated with different peptides was evaluated both in vitro and in vivo and correlated with the peptide physical and chemical properties. In vitro, these particles were internalized primarily through macropinocytosis. When the peptides were presented to bone marrow-derived dendritic cells they induce low immunoactivation relative to control cell penetrating peptides including the antennapedia homeodomain and TAT, as quantified by the expression of activation specific surface proteins like CD80, CD86 and major histocompatibility complex class II. In vivo, peptide decorated nanoparticles primarily accumulated in the lungs and the liver. Three human peptides derived from surfactant protein B; a lung surfactant protein, orexin; a neuropeptide hormone and lactoferricin; a globular glycoprotein that exist in many physiological fluids, facilitated the in vivo delivery of siRNA and induce significant knock down (90%) of a hepatocyte expressed protein, coagulation Factor VII.